Stitching space: a viaduct between the prison and the city - Arnot, Robyn (My University, 2010)
The South African prison system has, throughout its history, been notoriously exploited as a means for suppressing political resistance and warehousing criminals as labour commodities. The prison represented a microcosm of a divided country, racked by racial segregation and discrimination. Since the ejection of the apartheid state and the societal shift towards democracy, prison conditions have all but improved: the system has become wrought by overcrowding and chaos – largely attributed to the fi ercely regressive cycle of reoffending or ‘recidivism’ that has inhabited the power vacuum left by the eradication of the previous system. As South Africa’s prisons were constructed in an era that did not embrace the contemporary ideals of rehabilitation and restoration – since adopted by the Department of Correctional Services in an attempt to remedy the failing system – but rather in a period that maintained ‘correction’ through deterrence, they remain criminogenic repositories whose spaces cannot accommodate these progressive penal ideologies. The prison complex remains an anti-urban, asocial island, incessantly located and modelled on the archaic principles of the industrial city planners and social engineers, that without signifi cant reform, will continue to perpetuate the growing crisis of moral degeneration and the state’s losing battle against crime. This thesis intends to challenge and interrogate the seemingly inappropriate archetype of the prison by advocating a more pro-urban, more ideologically-relevant response to contemporary incarceration. The project will, both fi guratively and literally, and through the corrective lens of rehabilitation, attempt to shape the inbetween space – the no-man’s-land – that exists between the prison and the city, the criminal and conformist: a viaduct between bipolar entities traditionally accepted as disjointed, disengaged. Whilst serving as a pragmatic conduit for successful correction, the intervention will too attempt to traverse and suture the moat of indifference and prejudice that hinders the successful resettlement of prisoners that have duefully served their time.